Co-Delivery of Dragon's Blood and Alkanna tinctoria Extracts Using Electrospun Nanofibers: In Vitro and In Vivo Wound Healing Evaluation in Diabetic Rat Model - Rana Y. AlMotawa; Ghadeer Alhamid; Mohamed M. Badran; Raha Orfali; Abdullah H. Alomrani; Essam A. Tawfik; Dunia A. Alzahrani; Haya A. Alfassam; Safina Ghaffar; Amany Fathaddin; Areej Al-Taweel; Aliyah Almomen (MDPI AG, 2024)
The increasing prevalence of diabetic wounds presents a significant challenge due to the difficulty of natural healing and various obstacles. Dragon's blood (DB) and Alkanna tinctoria (AT) are well recognized for their potent healing abilities, which include potent antibacterial and anti-inflammatory activities. In this study, electrospun nanofibers (NFs) based on polyvinyl pyrrolidone (PVP) were co-loaded with both DB and AT, aiming to magnify their efficacy as wound-dressing applications for diabetic wound healing. The evaluation of these NFs as wound dressings was conducted using a streptozotocin-induced diabetic rat model. Electrospun NFs were prepared using the electrospinning of the PVP polymer, resulting in nanofibers with consistent, smooth surfaces. The loading capacity (LC) of AT and DB into NFs was 64.1 and 70.4 µg/mg, respectively, while in the co-loaded NFs, LC was 49.6 for AT and 57.2 µg/mg for DB. In addition, X-ray diffraction (XRD) revealed that DB and AT were amorphously dispersed within the NFs. The loaded NFs showed a dissolution time of 30 s in PBS (pH 7.4), which facilitated the release of AT and DB (25-38% after 10 min), followed by a complete release achieved after 180 min. The antibacterial evaluation demonstrated that the DB-AT mixture had potent activity against Pseudomonas aeruginosa (P. aeruginosa) and Staphylococcus aureus (S. aureus). Along with that, the DB-AT NFs showed effective growth inhibition for both P. aeruginosa and S. aureus compared to the control NFs. Moreover, wound healing was evaluated in vivo in diabetic Wistar rats over 14 days. The results revealed that the DB-AT NFs improved wound healing within 14 days significantly compared to the other groups. These results highlight the potential application of the developed DB-AT NFs in wound healing management, particularly in diabetic wounds.